Bounds For the Coefficients of Two New Subclasses of Bi-Univalent Functions - Abdullah, khalid Ibrahim; Mohammed, Nafya H. (Science Journal of University of Zakho, 2022)
This article discusses two new subclasses of the bi-univalent functions category ∑ in the open unit disk <img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAAcAAAAPCAYAAAAoAdW+AAAAAXNSR0IArs4c6QAAAGxlWElmTU0AKgAAAAgABAEaAAUAAAABAAAAPgEbAAUAAAABAAAARgEoAAMAAAABAAIAAIdpAAQAAAABAAAATgAAAAAAAACQAAAAAQAAAJAAAAABAAKgAgAEAAAAAQAAAAegAwAEAAAAAQAAAA8AAAAAiwx9kQAAAAlwSFlzAAAWJQAAFiUBSVIk8AAAAJpJREFUGBm90DEKwjAUxvFnURRE3cXZHqs36BGs5h7ugsfwAG7iUDpXJx0cRf/fIwEpdPXBLy95L21IzP4fA478YNs5umKdDRkCdp2mL9WcYBmbd/ICs7i2I5MDTpiixAWmL2+oscYLZ7SwTENfpGbK2qcbeKj4wAojr5jl5KfmOvONBgX2mOMKj987jmNNj+D/1wuFWExpo94XSF8VMPwwRFcAAAAASUVORK5CYII=" width="6" height="11">. The primary goal of the article is to obtain estimations of the coefficients <img src="data:image/png;base64,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" width="16" height="11"> and <img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAABMAAAAPCAYAAAAGRPQsAAAAAXNSR0IArs4c6QAAAGxlWElmTU0AKgAAAAgABAEaAAUAAAABAAAAPgEbAAUAAAABAAAARgEoAAMAAAABAAIAAIdpAAQAAAABAAAATgAAAAAAAACQAAAAAQAAAJAAAAABAAKgAgAEAAAAAQAAABOgAwAEAAAAAQAAAA8AAAAA71XDIwAAAAlwSFlzAAAWJQAAFiUBSVIk8AAAAN5JREFUOBHt078OwVAUx3EtkRgYJOIFjHaTyYrN6gUkBhuDP12NIuEtMLEwmAzCMxjYeQC+RyqpI1d6zX7JB7095+S22kjkH9s74NBwR9+2UdX3OHZjfHg4YAGbVCl+63H97o7NFFPPa9gPsz5b5DJ18iyUcUISU4SK3lmBrh2OaKOE0NHDWnRusEIGW6QwxAgNGKOH5aiUXVWQxR7y+MjQJZowRg9bU1lHETfIv5zABROM8TUDzs4DFXH/d/BbLlnu5xWyU0mwRx7a5wl5Azw5MCTNeg1nRDGDTpcF5wGtPR+YCS+jcAAAAABJRU5ErkJggg==" width="18" height="11">for the functions that are within these two new subclasses.